Analisis Yuridis terhadap Faktor Penegak Hukum dalam Praktik Hukum Acara Pidana - Mohd. Yusuf Daeng M.; Devira Geminilia Putri; Ichsan taufiqin; Vikri Pratama Ilyas (Journal on Education, 2023)
The criminal justice system is the process of enforcing material criminal law. In enforcing the criminal material law in a criminal justice system, it must be through the role of law enforcers. Law enforcement is an important part because without law enforcement, the law that has been agreed upon by the community will not be implemented. One part of the law in question is criminal procedural law. The law enforcers contained in the criminal procedural law are the Police, Advocates, Prosecutors (Public Prosecutors) and Judges. In this study, the role of law enforcers in criminal procedural law will be examined, which in this study consist of the Police, Advocates, Prosecutors (Public Prosecutors) and Judges. This research uses normative juridical research by linking the subject matter to the main topic in this study, namely the role of law enforcement factors in the practice of criminal procedural law. The results of this study will explain the role of relevant law enforcers in criminal procedural law and the role of law enforcers.